PHEDRA: using real-world data to analyze treatment patterns and ibrutinib effectiveness in hematological malignancies. (January 2018) - Garside, Jamie; Healy, Nollaig; Besson, Hervé; Hermans, Ruben; MacDougall, Finlay; Lestelle, Damien; Diels, Joris; Iraqi, Wafae
Aim: PHEDRA (Platform for Haematology in EMEA: Data for Real World Analysis) is a unique, noninterventional project based on secondary data collection from real-world (RW) patient-level (health record) databases to understand treatment patterns in hematological malignancies. It compares ibrutinib's effectiveness with alternative treatments using RW data (RWD) and randomized clinical trials data.Materials & methods: RWD are cleaned, validated, harmonized into a Common Data Model, and analyzed statistically alongside randomized clinical trial data. Treatment outcomes include overall and progression-free survival.Results: To date, RWD (four databases) are available for 2840 patients in three indications, collected between 1990 and 2017.Conclusion: PHEDRA is an innovative approach to generate evidence to inform optimal treatment decisions in RW settings.